Tailored Combinatorial Microcompartments through the Self‐Organization of Microobjects: Assembly, Characterization, and Cell Studies. Issue 16 (18th March 2019) - Song, Qimeng; Steuber, Marc; Druzhinin, Sergey I.; Schönherr, Holger
Abstract: A new concept enables the generation of cell microenvironments by microobject assembly at an water/air interface. As the orientation of 30 μm sized polymer cubes and their capillary force assembly are controlled by the surface wettability, which in turn can be modulated by coating the initially exposed surfaces with gold and self‐assembled monolayers, unique niches in closely packed arrays of cubes with vertex up orientation can be realized. The random assembly of distinctly different cubes, prefunctionalized or surface‐structured exclusively on their top surface, facilitates the parallel generation of different microenvironments in a combinatorial manner, which paves the way to future systematic structure–property relationship studies with cells. Abstract : Unique cell microenvironments were generated in a combinatorial fashion through the assembly of functionalized microcubes at an water/air interface and side‐wall‐selective surface functionalization. These results pave the way to future systematic structure–property relationship studies with cells.